2004
DOI: 10.1577/t03-028
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Reduced Early Marine Growth is Associated with Lower Marine Survival of Coho Salmon

Abstract: Coho salmon Oncorhynchus kisutch from the Strait of Georgia were used to test the hypothesis that slower growing fish in their first ocean year had lower survival over the late fall and winter than faster growing fish. The Strait of Georgia provided a suitable area for this study because it is a semi-enclosed rearing area for juvenile Pacific salmon that is distinct from the open marine rearing areas off the west coast. Coho salmon that survived the winter had significantly larger spacing between circuli on sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
215
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(229 citation statements)
references
References 27 publications
(31 reference statements)
12
215
1
1
Order By: Relevance
“…Perhaps growth rates continued to decline after 1991, but slow-growing Sockeye Salmon died at higher rates than did faster-growing Sockeye Salmon (Ruggerone et al 2005;Farley et al 2011) such that measured growth rates in the survivors did not decline. We suggest that Sockeye Salmon survivals began to decline after 1991 for many stocks because an increasing portion of the juveniles were unable to grow to the size (or possess sufficient energy reserves) required to survive some life history stanza, similar to the critical size hypothesis (e.g., Beamish et al 2004a). Further evidence of increasing competition is the increased proportion of Chilko Lake Sockeye Salmon returning late after three winters at sea instead of two.…”
Section: Irvine and Akenheadmentioning
confidence: 59%
“…Perhaps growth rates continued to decline after 1991, but slow-growing Sockeye Salmon died at higher rates than did faster-growing Sockeye Salmon (Ruggerone et al 2005;Farley et al 2011) such that measured growth rates in the survivors did not decline. We suggest that Sockeye Salmon survivals began to decline after 1991 for many stocks because an increasing portion of the juveniles were unable to grow to the size (or possess sufficient energy reserves) required to survive some life history stanza, similar to the critical size hypothesis (e.g., Beamish et al 2004a). Further evidence of increasing competition is the increased proportion of Chilko Lake Sockeye Salmon returning late after three winters at sea instead of two.…”
Section: Irvine and Akenheadmentioning
confidence: 59%
“…Slower growth in fishes has been correlated with a variety of life history traits, including higher mortality as the result of predation and starvation (22); reduced food availability as the result of gape limitations (23); usually, but not always, shorter life spans (13,24); increased age at sexual maturity and/or smaller size at maturity (25) and, because of the relationship between size and fecundity (e.g., ref. 26), reduced age-specific fecundity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have indicated that salmon that have poor early growth are less likely to survive (Beamish et al 2004b;Farley et al 2011;Jonsson et al 2011). Larger salmonids may be better able to avoid predation (Beamish and Mahnken 2001) and survive better than small salmonids when prey resources are low due to increased lipid stores (Farley et al 2007(Farley et al , 2011.…”
Section: Reduction Of Growth May Affect Survivalmentioning
confidence: 99%